2015
DOI: 10.1007/s12032-015-0486-1
|View full text |Cite
|
Sign up to set email alerts
|

GPCR48/LGR4 promotes tumorigenesis of prostate cancer via PI3K/Akt signaling pathway

Abstract: G-protein-coupled receptor (GPCR) 48, also known as leucine-rich repeat-containing G-protein-coupled receptor (LGR) 4, is an orphan receptor belonging to the GPCR superfamily, which plays an important role in the development of various organs and multiple cancers. However, the function of GPCR48/LGR4 in prostate cancer has not been fully investigated. Herein, GPCR48/LGR4 was overexpressed and silenced in prostate cancer cells via plasmid and shRNA transfection, respectively. The expression of GPCR48/LGR4 in mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…There is evidence in support of the participation of membrane receptors in the short-term effect on Cx-based channels (both GJCs and HCs). In some cases, the FA-mediated effect requires the participation of protein kinases that could be activated downstream of different GPCRs (Osmond et al, 2012; Suire et al, 2012; Liang et al, 2015), such as FA receptors (Itoh et al, 2003; Hirasawa et al, 2005). In agreement with such evidence, several protein kinases have been identified to modify Cxs (Solan and Lampe, 2014; Pogoda et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence in support of the participation of membrane receptors in the short-term effect on Cx-based channels (both GJCs and HCs). In some cases, the FA-mediated effect requires the participation of protein kinases that could be activated downstream of different GPCRs (Osmond et al, 2012; Suire et al, 2012; Liang et al, 2015), such as FA receptors (Itoh et al, 2003; Hirasawa et al, 2005). In agreement with such evidence, several protein kinases have been identified to modify Cxs (Solan and Lampe, 2014; Pogoda et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…[19] LGR4 promotes prostate tumorigenesis through PI3K/Akt signaling pathway. [16] Hsu et al identified a LGR4 splice variant which encodes a soluble secreted protein that can inhibit LGR4 mediated Wnt signaling. [27] Furthermore, a nonsense mutation of LGR4 (c.376C>T) has been reported to be strongly associated with low bone marrow density, electrolyte imbalance, reduced testosterone levels and increased risk of squamous cell carcinoma of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…[1215] The role of LGR4 in enhancing the aggressiveness of carcinoma as well as developmental derangements such as intrauterine growth retardation or renal development is well documented. [1619] It has also been verified as a prognostic factor for poor outcome in cancer patients. [20] In terms of ocular development, we demonstrated that knockout of LGR4 reduced epithelial cell proliferation and migration and resulted in EOB (eye open at birth) phenotype in mice.…”
Section: Introductionmentioning
confidence: 99%
“…In cervical carcinoma cells, it correlates with enhanced cell migration and metastasis [97]. In the case of skin and prostate, LGR4 promotes tumorigenesis by modulating MEK/ERK and Wnt/β−catenin pathways and the PI3K/Akt cascade, respectively [98,99]. In colorectal cancer, LGR4 expression is markedly upregulated in moderately and poorly differentiated cells as well as at the tumor invasive front and in metastasis and it significantly correlates with nodal spread in gastric cancer [100][101][102].…”
Section: Prognostic Value Of Lgrsmentioning
confidence: 99%